Turbidimetric Method for Measuring of Antibacterial Effect of 2-Methyl-4-(3,4 dihydroxy Phenyl)-Thiazole on the Growth Activity of Escherichia Coli and Pseudomonas Aeruginosa - Abbas, A.K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thiazoles are heterocyclic nitrogenous compounds, which were given a great attention due to their antibacterial effect, antihypertensive, stimulating glucose absorption (like antibiotics), acts as cytoprotective agent. The present work is conducted to evaluate the degree of antibacterial activity on the growth activity of Escherichia Coli (E.Coli) and Pseudomonas aeruginosa (P. aeruginosa) by incubation with 2-methyl-4-(3,4 dihydroxy phenyl)-Thiazole compound (MDHPT). Optical density (O.B) was measured by turbidmetric method, any increase in O.D would represent the increase in the bacterial growth .The results showed that there was a 75.7 % inhibition when using 190.4 ïg/ml (MDHPT) solution and 64.3% was obtained when using concentration of 369 ïg/ml. It has been concluded that (MDHPT) compound shows a bacterial biological activity.